Análise do equilíbrio e risco de quedas em idosos institucionalizados e não institucionalizados - Silva, Karen Cristina da (2021)
Introduction: Population aging has been increasing considerably over the years, it is a natural and inevitable process that can generate several changes, as the balance deficit and the risk of falls, being factors that interfere in the elderly's lifestyle influencing their autonomy for functional capacity. Objective: Analyze the balance and falling risk in institutionalized and non-institutionalized elderly. Method: This is a descriptive cross-sectional study. The study included 42 elderly, aged 60 years and over of both sexes, 21 institutionalized and 21 non-institutionalized. Balance and risk of falls were obtained through the tests: Time Up And Go, Poma-Tinetti and Sit and Stand Test. Data analysis was performed using the Shapiro-Wilk test, “U” of Mann-Whitney. The risk of falling among populations was evaluated. A value of p ≤ 0.05 was adopted as significant. Results: Relevant differences were found looking to the balance scores between the groups (p< 0.05). Conclusion: The results indicate that postural balance is lower in the institutionalized population, increasing their falling risk.